2021
DOI: 10.1038/s41380-021-01147-5
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid system mediates the association between gut-microbial diversity and anhedonia/amotivation in a general population cohort

Abstract: Anhedonia and amotivation are debilitating symptoms and represent unmet therapeutic needs in a range of clinical conditions. The gut-microbiome-endocannabinoid axis might represent a potential modifiable target for interventions. Based on results obtained from animal models, we tested the hypothesis that the endocannabinoid system mediates the association between gut-microbiome diversity and anhedonia/amotivation in a general population cohort. We used longitudinal data collected from 786 volunteer twins recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…Gut microbiota has been shown to produce eCBs and many bioactive lipids that structurally and functionally resemble eCBs (Cani et al, 2016 ; Sharkey and Wiley, 2016 ). Given that the eCB system plays an important role in energy metabolism and inflammation, it may act as a promising therapeutic target for many neurological diseases (Minichino et al, 2021 ). In this study, we observed that AEA and many expanded eCBs showed significant decreases in the blood when pain and its associated cognitive deficits occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota has been shown to produce eCBs and many bioactive lipids that structurally and functionally resemble eCBs (Cani et al, 2016 ; Sharkey and Wiley, 2016 ). Given that the eCB system plays an important role in energy metabolism and inflammation, it may act as a promising therapeutic target for many neurological diseases (Minichino et al, 2021 ). In this study, we observed that AEA and many expanded eCBs showed significant decreases in the blood when pain and its associated cognitive deficits occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that AEA can attenuate SEB-mediated ARDS in a mouse model by targeting miRNA which triggers anti-inflammatory pathways involving immunosuppressive cells, such as the myeloid-derived suppressor cells (MDSCs) and the regulatory T cells (Tregs) [ 9 ]. Recent studies have shown that the diversity of the gut microbiota may be regulated by endocannabinoids [ 19 , 26 ]. This raises an important question of whether endocannabinoids can alter the microbiota in the gut and the lungs during ARDS, thereby providing increased protection from pathogenic bacteria as well as suppressing hyperinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the authors tested the hypothesis that either reduced serum levels of PEA or increased stool levels of PEA would mediate the association between microbial diversity and anhedonia/amotivation. Indeed, the association was found to be mediated by faecal, but not serum, levels of PEA [179].…”
Section: Microbiome-gut-brain Axis and Endocannabinoidome: "Omics" Interactions Go Centralmentioning
confidence: 89%
“…From a large cohort study on nearly 800 volunteer twins it has recently emerged that the eCBome mediates the relationship between gut microbiome and anhedonia/amotivation [179]. In particular, the authors tested the hypothesis that either reduced serum levels of PEA or increased stool levels of PEA would mediate the association between microbial diversity and anhedonia/amotivation.…”
Section: Microbiome-gut-brain Axis and Endocannabinoidome: "Omics" Interactions Go Centralmentioning
confidence: 99%